Long COVID-19 in children: a review of key information - Głowinkowska, Monika; Machura, Edyta; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Long COVID in children is defined as a syndrome of persistent symptoms following SARS-CoV-2 infection, which appear within three months after the acute phase, last for at least two months, and have a significant impact on the child’s daily functioning. The symptoms are heterogeneous and may involve multiple organ systems. The causes and risk factors for developing long COVID in the paediatric population remain incompletely understood, and diagnosis may be challenging due to the nonspecific nature of symptoms and the need for thorough differential diagnosis. Further long-term studies are required to establish the true association between acute SARS-CoV-2 infection and the development of long COVID in children. This paper presents fundamental information on long COVID in the paediatric population, with a focus on key risk factors, pathophysiology, clinical manifestations, diagnostic approaches, the importance of vaccination, and the potential role of viral variants in the pathogenesis of long COVID.